2016
DOI: 10.3390/ma9100815
|View full text |Cite
|
Sign up to set email alerts
|

TiC Reinforcement Composite Coating Produced Using Graphite of the Cast Iron by Laser Cladding

Abstract: In this study, a TiC-reinforced composite coating was produced to improve the wear resistance of a pearlite matrix grey iron using a pre-placed Ti powder by laser cladding. Results of scanning electron microscopy (SEM), X-ray diffractometer (XRD), and energy dispersive X-ray spectroscopy (EDS) confirmed that the coating was composed of TiC particles and two kinds of α-Fe phase. The fine TiC particles were only a few microns in size and uniformly distributed on the matrix phase in the composite coating. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Consequently, several studies have been directly focused on a fabrication of such composite layers via laser surface treatment processes. Liu et al [15] produced TiC-reinforced surface layers on a grey cast iron substrate using LSA with a pre-placed titanium powder. The resulting composite layers had a significantly higher wear resistance to that of the substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several studies have been directly focused on a fabrication of such composite layers via laser surface treatment processes. Liu et al [15] produced TiC-reinforced surface layers on a grey cast iron substrate using LSA with a pre-placed titanium powder. The resulting composite layers had a significantly higher wear resistance to that of the substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…There are two possible sources of the TiC phase: one is the unfused original TiC ceramic particles, the other is the second precipitated phase. Ther TiC has high hardness, which is beneficial to the mechanical properties of the coatings; therefore, it has been reported that TiC-reinforced metal matrix composite coatings offer significant progress in terms of average micro-hardness and wear resistance [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…High C contents in cast iron substrates provide excellent conditions for the in situ formation of MMC surface layers via LA, with elements that tend to form carbides. Several studies on the LA of cast iron substrates have focused on the in situ synthesis of TiC-reinforced layers (TRLs) by introducing Ti into the molten pool [ 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. From the point of view of the wear properties, the microstructure of the synthesized TRLs should contain a martensitic matrix with homogeneously-dispersed TiC precipitates [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%